2019
DOI: 10.26434/chemrxiv.8125031.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Golden Opportunity: A Clickable Azide-Functionalized [Au25(SR)18]-Nanocluster Platform for Interfacial Surface Modifications

Abstract: Ultrasmall atomically precise monolayer-protected gold thiolate nanoclusters are an intensely researched nanomaterial framework, but there is a lack of a system that can be directly synthesized and undergo interfacial surface chemistry. We report an [Au<sub>25</sub>(SCH<sub>2</sub>CH<sub>2</sub>-<i>p</i>-C<sub>6</sub>H<sub>4</sub>-N<sub>3</sub>)<sub>18</sub>]<sup>-</sup> nanocluster platform with azide m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…With a further increase in the concentration of the reducing agent (0.32 M NaBH 4 and above), rapid precipitation takes place and the solution turns clear immediately (i.e., no clusters remain in solution). We have previously shown that Au 25 (SR) 18 NCs are much more stable in high concentrations of NaBH 4 than larger NCs; 7 we believe that higher NaBH 4 concentrations lead to preferential precipitation of larger NCs during the synthesis, which may be either due to the reductive removal of thiolates off their surfaces or the poorer solubility of the larger NCs. Similar results have been previously reported for the Au 25 (MUA) 18 system (where MUA = mercaptoundecanoic acid).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…With a further increase in the concentration of the reducing agent (0.32 M NaBH 4 and above), rapid precipitation takes place and the solution turns clear immediately (i.e., no clusters remain in solution). We have previously shown that Au 25 (SR) 18 NCs are much more stable in high concentrations of NaBH 4 than larger NCs; 7 we believe that higher NaBH 4 concentrations lead to preferential precipitation of larger NCs during the synthesis, which may be either due to the reductive removal of thiolates off their surfaces or the poorer solubility of the larger NCs. Similar results have been previously reported for the Au 25 (MUA) 18 system (where MUA = mercaptoundecanoic acid).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…We have shown that using higher concentrations of the reducing agent (NaBH 4 ) in the original synthesis of Fmoc-Gly-CSA-functionalized Au NCs leads to smaller NCs and narrow size distributions. At a concentration of 0.30 M NaBH 4 , Fmoc-Gly-CSA-functionalized Au 25 (SR) 18 NCs have been synthesized which have characteristic UV−vis absorption peaks at 690, 440, and 390 nm and core sizes of 1.1 ± 0.2 nm. Fmoc deprotection gives stable Au NCs with primary amine functional groups on the surface with no significant change of the NC size or UV−vis spectral signature.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the identification of every ligand in the ligand shell, it is possible to precisely functionalize the surface of Au 25 NCs by site-specific ligand exchange. 58 Recently, a clickable azidefunctionalized [Au 25 (SR) 18 ] − was reported (Figure 2i), 48 in which the N α 's of the azide moieties ligated on the phenyl rings make an average C−C−N α angle of ∼122.7°, indicating the primarily sp 2 character of the N α , and the N α −N β −N γ is almost linear, as indicated by SCXRD. Such a configuration enables the full amenability of azide moieties to strain-promoted alkyne−azide cycloaddition chemistry.…”
Section: Ligand Assembly On the Surface Of Nanoclustersmentioning
confidence: 97%
“…Besides these methods, surface reactions have also received significant attention in recent years; however, there are few reports on such reactions, two of which are azido-and amide-bond formation reactions. 18,19 The Menshutkin S N 2 reaction is a common method to obtain the quaternary ammonium salt ([−N(CH 3 ) 3 ] + ) by reacting a tertiary amine with an alkylating agent. 20 In this study, we demonstrate the Menshutkin (methylation) reaction of the surface pyridyl (Py) moieties on basic Au 25 (4-PyET) 18 clusters (4-PyET = −SCH 2 CH 2 Py) for their successful transformation into cationized Au 25 (4-PyET-CH 3 + ) x (4-PyET) 18-x (x ≈ 18) clusters (Scheme 1).…”
mentioning
confidence: 99%